The Effect of Functional Value and Epistemic Value on Tourist Satisfaction of Lake Toba - Saragih, Megasari Gusandra; Surya, Elfitra Desy; B., Mesra (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The study was studied to determine the effect of functional value and epistemic value on tourist satisfaction of the super priority tourist attraction of Lake Toba. The problem is finding a decrease in the number of tourist visits to the super priority tourist attraction of Lake Toba during the covid-19 pandemic. Where the amount of samples is 100 tourists who have visited Lake Toba, with a nonprobability sampling technique with a purposive sampling approach. Multiple linear regression became the model of this research using SPSS 24.0 analysis tool. The results of the study found that functional value and epistemic value had a major effect on tourist satisfaction within the super priority tourism of Lake Toba.